Universities and knowledge intensive business services as actors of the creative regional technological infrastructure: The case of the Upper-Rhine Valley - Jean-Alain Heraud; Emmanuel Muller (European Regional Science Association (ERSA), 1998)
Characterizing the innovative capacity of a territory, and his specific attractivity for external direct investment in new fields, needs the definition of measurable concepts and the design of a proper methodology to gather relevant quantitative data. The aim of the paper is to propose a general theoretical view of the functional characteristics of the various actors and institutions that compose the ?technological infrastructure? of a region, then to show some results of studies made in the Upper-Rhine Valley (in France as well as in Germany) that cast a light on the contribution of certain important players like universities and ?knowledge intensive business services?. Universities have an important and very composite economic impact in their region. As a regular public administration they contribute to local economic activity throug personal incomes, capital expenses and current expenses. But they also attract students, contribute to the image of the city and sometimes propose valuable services for firms. Where universities (and public research centers associated to them) play a very specific role is by training young researchers, who are at the same time inputs and outputs of the research process and fulfill an important role in the cooperation and transfer networks with the most creative local firms. New types of knowledge intensive services are increasingly developed in the environment of industrial firms, either as a result of the process or of ?externalization? of large firms or as an autonomous process of creation ? for instance start-ups initiated by the academic system, but other sorts of services too. These business services could play a crucial role not only for large technology based firms, but also for the small firms at the basis of the regional industrial fabrique. They participate to the technological infrastructure, and more largely to the managerial skills? supply and the innovative climate of the territory.
Keywords: 330